Developing Students’ Prosocial Behavior Through Collaborative Teamwork Teaching - Muhammad, Asrori; Effendy, Chairil (Advances in Social Sciences Research Journal, 2021)
Developing students’ prosocial behavior is a very important program in the living situation that increasingly complicated, individualistic, and hedonistic. It is important because prosocial behavior refers to voluntary actions that intended to help or benefit another individual or group of individuals. The present study was designed to examine the effectiveness of a collaborative teamwork teaching to develop the prosocial behavior of elementary school students. It was an experimental study with one group pretest-posttest design. The experiment was carried out in three elementary schools. They were Islamic Al-Azhar Elementary School (SD Islam Al-Azhar), State Elementary School 34 (SD Negeri 34), and Muhammadiyah Elementary School (SD Muhammadiyah) Pontianak. There were four aspects of the students’ prosocial behavior to develop. These aspects were sharing, helping, cooperating, and caring. The results of the study showed that the collaborative teamwork teaching was effective to develop the prosocial behavior of students in three elementary schools. All of the investigated aspects got improved. They were categorized “high”, except the aspect of caring. It was classified as “medium”.